Some Aspects Of The Biology Of Ikan Baung, Mystus Nemurus C. &. V. With Reference To Chenderoh Reservoir - Khan, Mohammad Salim (1987)
Some aspects of the biology of Ikan Baung, Mystus nemurus C. & V. including taxonomy, food and feeding habits, reproduction, growth and its ecology were studied. The fish is a bottom feeder and fed extensively on a wide range, of food items that include teleosts, crustaceans, benthic invertebrates and detrital materials. The relative gut index has been found to vary from the lowest 0.783 to the highest 1.07 in a size range of 8 . 2 to 67. 0 cm. External fertilization and heterosexuality are exhibited. Sexual differentiation can be made depending on visual observation of secondary sex characters. Five maturing stages have been identified. Size at first sexual maturity has been found within the length range of 3 2 . 5 t o 3 5. 5 cm in case of female and 35 .5 to 38.5 cm in male. Fecundity has been found to vary from 6 , 900 to 93 , 510 in specimens having a length range of 34 .8 to 45 cm . The relationship between Fecundity, F, and Length, L can be expressed as F = 0.00 11L4.758 The fish i s a partial spawner and spawning period has been found long and indefinite. The ripe oocytes are therefore shed off within an interval of time. No major spawning season can be detected as is evidenced from the seasonal fluctuation of gonadosomatic index , ovadiameter measurements and different maturity stages. Fat contents in the abdominal mesentaries are associated mainly with maintenance and also for reproduction.